IPA of Communication Experience of Women Leaders in Collaborative Meetings in Software Engineering Teams - Sarmento, Camila; Massoni, Tiago; Dantas, Carlos; Araújo, Narallynne; Rocha, Rayana (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2024: Anais do XXXVIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2024.3508, 2024)
Context: Software development is an inherently collaborative activity, where interactions among team members are crucial for project success. Concurrently, studies have explored the relationship between gender and communication, especially in organizational contexts, involving the participation of women as a mitigating factor for communication and organizational problems in development teams. Their results indicated that, although the presence of women was considered less relevant compared to team experience and size, qualitative data emphasized their significance. However, there is still a significant gap regarding the experiences of women leaders facing communication challenges during collaborative meetings in software development teams. Objective: Therefore, the aim of this research is to investigate the experiences of women leaders in collaborative meetings of software development teams, focusing on the communication challenges they face. To achieve this objective, Method: we opted to employ a methodology underexplored in the field of software engineering: Interpretative Phenomenological Analysis (IPA). This approach focuses on deeply understanding the nuances of experiences lived by these five women leaders, seeking to comprehend not only the superficial aspects of interaction but also the underlying meanings attributed by them to these experiences. Through IPA, we conducted a meticulous analysis of the challenges narrated by the participants, aswell as the strategies they adopted for effective communication during collaborative meetings. This data was carefully grouped, allowing the identification of gaps in the literature and providing valuable insights for possible future research in the field of software engineering. Results: Preliminary findings reveal various communication challenges faced by them, including pressure to prove competence, lack of recognition and validation of their contributions, dominant attitudes from male managers, and resistance to change. Conclusion: The results highlight the need for interventions to support and value female leaders, as well as promote more flexible and responsive management. It is suggested that future work delve deeper into these issues, and, to this end, research questions are proposed to guide further investigations.